Pengaruh Risiko Kredit dan Risiko Likuiditas Terhadap Profitabilitas Bank - Dewi, Eneng Trisnawati; Srihandoko, Wimpi (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
Banks in it’s operations are certainly unfree from various risks. The Bank's business risk is uncertainty about a predictable or unpredictable outcome. Non-Performing Loans (NPL) Are financial ratios related to credit risk. Loan to Deposit Ratio (LDR) is a financial ratio related to liquidity risk. This study aims to examine the relationship between credit risk and liquidity risk to profitability at 3 government banks. The data in this study are secondary data. The results of this study indicate that partially credit risk has a significant effect on profitability, and liquidity risk has no significant effect on profitability. Credit risk and liquidity risk simultaneously have an influence on profitability. Keywords: non performing loan, liquidity risk, profitability